KESADARAN EKOLOGI DALAM MITOS DI TELAGA RAMBUT MONTE DESA KRISIK, KECAMATAN GANDUSARI, KABUPATEN BLITAR - Fitrahayunitisna, Fitrahayunitisna (Studi Budaya Nusantara, 2019)
Abstract Myth as a folklore is a genre of oral literature. Myth on Java is a story that contains Javanese beliefs about occult things. The interesting thing about the myths of Rambut Monte is the values impicitly related to ecological consciousness. It is also related to consciousness of society about sustainably environment. The myths that people believe in Rambut Monte implicate for sustainability of nature. This is related to the roles and functions of the myth. This research is a descriptive qualitative study. The qualitative data collected by interview, observation, and study of documentation. Step of analizing data started by transcribing the result of interview from informants. Then, the results of the transcript were translated. Data from observation and documentation are reorganized as a secondary data. The myths found in this study are the myths about origins name of Rambut Monte, holy lake water, the God fish, old trees, and the danyang of Rambut Monte. The ecological consciousness are found in the myths are about the value of respecting nature, conservation values, the value of respecting living things, and the value of ecological harmony. The myths are play the role and function as a media to educate and spread a message to community abaut the ecological consciousness. Therefore, these myths are also has a role as disequilibrium decomposer between human and nature.